Qualitative Methodologies in Organization Studies Volume II: Methods and Possibilities (Springer International Publishing, 2018)
'This current and timely collection brings together an impressive group of contributors, providing us with a comprehensive and detailed view of qualitative methods as practiced today; of benefit to any qualitative researcher in business and management. Highly recommended.' -Yochanan Altman, Professor of International HRM, Middlesex University, UK 'This book is a carefully curated cornucopia of insights for both early career and experienced qualitative researchers seeking to understand the complex social and organizational world we live in.' -Rob Wilson, Chair of Information Systems Management and Director of the Knowledge Innovation Technology Enterprise Research Centre, Newcastle University, UK 'The editors provide us with an inspiring reservoir of intellectual knowledge on how, when and why we apply qualitative methods in organizational studies. The book is highly recommended for researchers interested in organizations - or other social settings - to dive into this reservoir of approaches and theories.' -Ann Westenholz, Professor Emeritus, Copenhagen Business School, Denmark This book provides a thorough review of tested qualitative methods often used in organization studies, and outlines the challenges and essential requirements of designing a qualitative research project. The methods examined include case studies, observation, interviewing and the repertory grid technique. By highlighting certain key 'rules' for carrying out qualitative research and describing issues that should be avoided, this second volume of Qualitative Methodologies in Organization Studies is essential reading for academics and researchers who wish to understand the current state of qualitative data gathering within organization studies. Those exploring organization studies will find this two-volume collection extremely valuable as it contains robust contributions from highly-skilled authors who are actively researching in this field.